Accurate prediction equation to assess body fat in male and female adolescent football players - Lozano-Berges, G.; Matute-Llorente, A.; Gómez-Bruton, A.; González-Agüero, A.; Vicente-Rodriguez, G.; Casajús, J. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
The aims of this study were (a) to determine which of the most used anthropometric equations was the most accurate to estimate percentage of body fat (%BF), (b) to develop a new specific anthropometric equation, and (c) to validate this football-specific equation. A total of 126 (13.3 ± 0.6 years) football players (86 males and 40 females) participated in the present study. Participants were divided into two groups: 98 players were included in the assessment of existing equations and in the development of the new prediction equation, and 28 players were used to validate it. %BF was measured with dual-energy X-ray absorptiometry (DXA) and also estimated with six different %BF anthropometric equations: Johnston, Slaughter, Carter, Faulkner, Deurenberg, and Santi-Maria. Paired t tests were used to analyze differences between methods. A football-specific equation was developed by a stepwise linear regression. The existing anthropometric equations showed significant bias for %BF when compared with DXA (p < .001; constant error ranged from -4.57% to 9.24%; standard error of estimate ranged from 2.46 to 4.20). On the other hand, the developed football-specific equation was %BF = 11.115 + 0.775 (triceps skinfold) + 0.193 (iliac crest skinfold) - 1.606 (sex). The developed equation demonstrated neither %BF differences (p = .121; constant error = 0.57%; standard error of estimate = 0.36) when compared with DXA, presenting a high cross-validation prediction power (R2 = .85). Published anthropometric equations were not accurate to estimate %BF in adolescent football players. Due to the fact that the developed football-specific equation showed neither differences nor heteroscedasticity when compared with DXA, this equation is recommended to assess %BF in adolescent football players.